2018
DOI: 10.1111/febs.14660
|View full text |Cite
|
Sign up to set email alerts
|

The structure of INI1/hSNF5 RPT1 and its interactions with the c‐MYC:MAX heterodimer provide insights into the interplay between MYC and the SWI/SNF chromatin remodeling complex

Abstract: c-MYC and the SWI/SNF chromatin remodeling complex act as master regulators of transcription, and play a key role in human cancer. Although they are known to interact, the molecular details of their interaction are lacking. We have determined the structure of the RPT1 region of the INI1/hSNF5/BAF47/SMARCB1 subunit of the SWI/SNF complex that acts as a c-MYC-binding domain, and have localized the interaction regions on both INI1 and on the c-MYC:MAX heterodimer. c-MYC interacts with a highly conserved groove on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…1), and in line with recent NMR-based studies showing that the imperfect repeats of SNF5—which are required for this activity (Fig. 1b)—recognize the DNA-binding surface of the MYC:MAX bHLHZip heterodimer in a manner that is mutually exclusive with DNA recognition 42 . What we do not know, however, is the biochemical context in which SNF5 tempers MYC in cells.…”
Section: Discussionsupporting
confidence: 88%
“…1), and in line with recent NMR-based studies showing that the imperfect repeats of SNF5—which are required for this activity (Fig. 1b)—recognize the DNA-binding surface of the MYC:MAX bHLHZip heterodimer in a manner that is mutually exclusive with DNA recognition 42 . What we do not know, however, is the biochemical context in which SNF5 tempers MYC in cells.…”
Section: Discussionsupporting
confidence: 88%
“…The N-terminal region of hSNF5 from His171 to Val185 lacks medium-and long-range nuclear Overhauser effects (NOEs) and it remains unstructured in the solution structure of free hSNF5 . Except for the N-terminal loop regions, our solution structure of hSNF5 171-258 is similar to the previously reported hSNF5 RPT1 structures covering 184-249 residues (PDB code 5L7A) [35], forming a β1β2α1α2 fold, with a Cα RMSD of 2.0 Å for the 64 atoms between Glu184 and Tyr248 ( Figure 2E,F). The hSNF5 171-258 /BAF155 SWIRM complex also eluted at an even higher molecular weight than the heterodimer from SEC ( Figure 2G), but the absolute molar mass of the hSNF5 171-258 /BAF155 SWIRM complex was found to be 22.5 ± 1.6 kDa from MALS data, which confirmed that hSNF5 171-258 and BAF155 SWIRM form a heterodimer (calculated m.w.…”
Section: Hsnf5 171-258 and Baf155 Swirm Form A Heterodimersupporting
confidence: 86%
“…For both hSNF5 171-258 and BAF155 SWIRM , the sequence in Hs is identical to that in Mm. A previous report describing the crystal structure of the hSNF5 169-252 /BAF155 SWIRM complex found that these proteins form a heterotetramer [34], whereas the size exclusion chromatography (SEC) and multi-angle light scattering (MALS) data have indicated that hSNF5 184-249 is a monomer [35]. We performed SEC and MALS experiments with different constructs of hSNF5 in complex with BAF155 SWIRM to investigate this discrepancy.…”
Section: Hsnf5 171-258 and Baf155 Swirm Form A Heterodimermentioning
confidence: 87%
See 1 more Smart Citation
“…High-resolution structural studies of the SWI/SNF family of remodelers had until recently been limited to fragments, such as the Arp module (Arp7, Arp9 and some combination of Rtt102 and HSA helix of Snf2 [paralog to Sth1]) (Schubert et al, 2013), the SwiB domain of the human SMARCD (homolog of Rsc6), the WH domain of SMARCB (homolog of Sfh1) (Allen et al, 2015), the SWIRM domain of Swi3 (paralog of Rsc8) (Da et al, 2006), the RPT domain of SMARCB (homolog of Sfh1) (Sammak et al, 2018), the SWIRM-RPT complex of SMARCC-SMARCB (homologs of Rsc8 and Sfh1) (Yan et al, 2017), the SANT domain of SMARCC (homolog of Rsc8), and the ATPase of Snf2 (homolog of Sth1) on its own (Dürr et al, 2005;Xia et al, 2016) and in complex with a nucleosome with different ATP analogs (Liu et al, 2017;Li et al, 2019). Early structural studies of full SWI/SNF remodeling complexes by negative stain electron microscopy (EM) were limited by low resolution and/or reconstruction artifacts (Chaban et al, 2008;Dechassa et al, 2008;Asturias et al, 2002;Leschziner et al, 2007;Leschziner et al, 2005;Skiniotis et al, 2007;Smith et al, 2003), with only one study able to map the location of some subunits within the complex (for the yeast SWI/SNF complex using subunit deletion) (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%